Design and construction of a mini fuel cell for interference detection and a hybrid solar / fuel cell / battery multi purpose emergencey kit - Gan, Yong Kiong (Universiti Malaysia Sarawak (UNIMAS), 2008)
In this research, two mini Proton Exchange Membrane fuel cell (PEMFC) and Alkaline Fuel Cell (AFC) were analyzed and used as an alternative source for some small mechatronic applications.